IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MENINGKATKAN KEPEDULIAN SOSIAL SISWA DI SMA DARUL KAROMAH - Taufikurrahman Taufikurrahman; Al Amin Nur Rofiq (LP2M IAI Miftahul Ulum Pamekasan, 2020)
Moral decadence has been rampant in world education so that it has become a blurry portrait in the world of education. The dire situation and condition of the nation's character has prompted the government to take the initiative to prioritize national character development. The cheapest in the 2005-2025 National Long-Term Development Plan, namely